Exploring the role of exercise on thyroid function, postural control, and neuroplasticity in individuals with hypothyroidism - Watson-van Zyl, Jeanine (Stellenbosch : Stellenbosch University, 2022)
Thesis PhD (Sport Sc)--Stellenbosch University, 2022.